Unlocking the Innovative and Commercialization Potential of the Undergraduate Final Year ‘Design and Make’ Research Projects - Svubure, Oniward; Pedzisai, Constantino (Innovare Journal of Education, 2023)
Innovation and commercialization are viewed as key drivers of any country’s economy. Individuals normally start commercial enterprises with an innovative and entrepreneurial mindset. Universities worldwide are regarded as centers of knowledge creation and are expected to play a key role in the industrialization of a country’s economy. For undergraduate engineering students, the capstone ‘design and make’ research module is best placed to unlock their innovative and commercialization potential. Capstone modules are typically about applying what the student has learned during the entire course of studies, thereby presenting a rich setting for innovation and entrepreneurial skills learning. In Zimbabwean universities, the final year capstone project is offered where the student fabricates a product as a possible solution to a problem in industry. However, very few of the ideas from the module have found their way into the real world as goods or services. The study’s main question was to establish the extent of the impact of the projects module on agricultural engineering undergraduate students’ innovative and commercial-mindedness. Using the case study research design, data was collected on implementing the capstone module at the Chinhoyi University of Technology’s Department of Agricultural Engineering. Data was collected on the parameters potentially impacting the student’s innovativeness and commercial mindedness. The study findings showed that in its present form, the research project module improves the students’ design and innovative skills. At the same time, equipping the same scholars with entrepreneurial skills is inadequate.